Bounce back. 2, No such thing as perfect - Misako Rokkusu, 1977- (Bounce back, 2023)
Emma can't help comparing herself to her bright and popular older sister, Julia. Try as she might, Emma can't seem to please her mom as much as her sister does. With help from her friends and basketball teammates, as well as Lexi, the French bulldog she's dogsitting, Emma realizes that there's no such thing as "perfect"--and it feels better to be true to herself, instead of trying to please others"--